O5-S3.06 Testing for STIs in population-based sexual health surveys without returning results: development of an ethical and pragmatic approach. (10th July 2011) - Field, N; Tanton, C; Mercer, C; Nicholson, S; Sjordin, S; Soldan, K; Beddows, S; Ison, C; Johnson, A; Sonnenberg, P
Abstract : Background: Sexual health surveys are enhanced by biological measures, such as non-invasive testing for STIs. The Third British National Survey of Sexual Attitudes and Lifestyles (Natsal 3) will estimate the population prevalence of five STIs ( C trachomatis, N gonorrhoeae, type-specific Human Papilloma Virus, HIV and M genitalium ) in a probability sample aged 16–44 y. This raises complex ethical issues, including return of results, testing in under-18s, appropriate consent and confidentiality. We describe the development of an ethically sound and acceptable approach to urine testing for STIs, without returning results, in Natsal 3. Methods: The Natsal team considered the following: (1) more appropriate settings to obtain free STI testing and advice are now widely available, (2) survey conditions and sample type limit accuracy and timeliness, (3) for some STIs, the clinical and public health implications are unknown, (4) a uniform approach is easier to explain and be understood, (5) non-return of results is more cost efficient, enabling wider STI testing, (6) practical difficulties in returning results, (7) non-clinical interviewers. This rationale was subjected to peer-review as part of the funding process, stakeholders were engaged, and it was then submitted to a research ethics committee (REC). Piloting was performed in the general population to test acceptability and feasibility. Findings The agreed approach involved written consent for voluntary anonymised testing with the knowledge that results are not returned and the option of sample storage for future research. Confidentiality was assured by keeping STI data and personal identifiers at separate institutions, and a detailed protocol was designed to ensure that STI data were irreversibly unlinked after 3 months. In piloting, 61% (68/111) of participants agreed to provide a sample and 93% (63/68) agreed to sample storage for future research. All participants were given information about accessing clinical tests and STI advice. Conclusions: The testing of STIs and the decision not to return results was accepted by a REC, in the context of a stakeholder consensus, and was acceptable to participants in developmental pilot work. Our experiences, both in developing the approach, and in the mechanisms to achieve this, may inform the ethical considerations of researchers, RECs and funders in study design and ethical approaches to population-based biological sampling.